Improved Method of Ink-Gelatin Perfusion for Visualising Rat Retinal Microvessels - Jianbin, Tong (Japan Society of Histochemistry and Cytochemistry, 2008)
To visualize completely rat retinal microvessels, the gelatin-ink perfusion condition was systematically optimized using von Willebrand factor (vWf) immunostaining as control. Whether the vessel showed by the new perfusion condition can be used for double label with neurons or glial cells in the same retina was also tested. Our results showed that infusing rats first with 20 ml of 37°C ink plus 3% gelatin at 140% rat mean arterial pressure (MAP), and subsequently with 20 ml of 37°C ink plus 5% gelatin at 180% rat MAP allowed the ink to completely fill the rat retinal microvessels. Rat retinal microvessels labeled by the perfusion method were more in number than that by vWf immunostaining. Moreover, our data, for the first time, displayed that the improved gelatin-ink perfusion had no effect on and caused no contamination to the following fluorogold labeling or immunostaining of retinal neurons or glial cells in the same tissue. These data suggest that the improved gelatin-ink perfusion technique is a superior method for morphological characterization of rat retinal microvessels, compatible to the double labeling of glial cells and neurons, and it extends the practical scale of the classic method.